The Effects of House Prices and Home Equity Extraction on Career Outcomes - Cespedes, Jacelly; Liu, Zack; Parra, Carlos (The Review of Corporate Finance Studies, 2026)
This paper investigates the effects of housing wealth shocks on workers’ career decisions related to job quality and long-term career outcomes. Using a novel data set of career histories in the film industry, we find that homeowners facing greater house price declines reduce participation in high-quality projects but increase involvement in low-quality films. Conversely, renters are not affected by these shocks. Consistent with individuals using home equity during job searches, these shocks have a greater impact on homeowners who extracted home equity during the housing boom. Moreover, house price declines from the housing crisis affect long-term career paths. (JEL J01, R20, D14, G51)